Development of an adaptive differential protection scheme for transformer during current transformer saturation and over‐fluxing condition. (17th December 2020) - Raichura, Maulik; Chothani, Nilesh; Patel, Dharmesh
Summary: Despite having several modern transformer protection schemes, the protection engineer prefers the universally adopted unit‐type differential protection scheme for the current transformer (CT) because of its functional flexibility. Inrush condition, external fault with current transformer saturation, over‐fluxing, or the combination of these may maloperate the unit‐protection schemes. In this article, all the above‐mentioned situations have been addressed that mislead differential protection. A multifunctional algorithm is presented that filters the disturbance for correct relay operation. The inrush condition is carefully examined with the help of the average angle of the differential current. Moreover, an adaptive algorithm takes care of the false operation of the transformer protection scheme during an external fault with CT saturation condition. Also, the momentary over‐fluxing condition is dealt with, with the help of fifth‐ and seventh‐harmonic‐based analysis of the differential current. Hence, the disturbance will be thoroughly examined and a decision signal issued accordingly to avoid unnecessary isolation of the transformer to improve system stability. The power system is simulated in PSCAD software and the algorithm is developed in MATLAB. Moreover, the proposed scheme is validated on a hardware prototype for authentication. It is found that the proposed scheme provides acceptable results and can be implemented in the real field. Abstract : The power system along with transformer is simulated in PSCAD software and the algorithm is developed in MATLAB software. Various test cases of normal load, magnetic inrush, over‐fluxing, internal fault as well as an external fault with current transformer saturation are simulated. A multifunctional adaptive algorithm has been presented which effectively filters the internal fault for correct relay operation from external disturbance.